2021
DOI: 10.1055/a-1551-6930
|View full text |Cite
|
Sign up to set email alerts
|

Perylene Monoimide as a Versatile Fluoroprobe: The Past, Present, and Future

Abstract: Perylene dyes have transcended their role as simple colorants and have been reinvigorated as functional dyes. Based on the substitution at the peri position by six-membered carboxylic imides, the perylene family is principally embellished with perylene diimides (PDIs) and perylene monoimides (PMIs). Perylene dyes are widely acclaimed and adorned on account of their phenomenal thermal, chemical, and photostability juxtaposed with their high absorption coefficient and near-unity fluorescence quantum yield. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 80 publications
(148 reference statements)
0
20
0
Order By: Relevance
“…[10] At the same time, perylene monoimide (in this work abbreviated as "P") has attracted less research attention. [11] Perylene monoimides also have a strong absorption in the visible range, but have higher lying LUMO energy levels (lower reduction potentials) than perylene diimides. [12] This enables reaching of higher open circuit voltages (V OC ) in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[10] At the same time, perylene monoimide (in this work abbreviated as "P") has attracted less research attention. [11] Perylene monoimides also have a strong absorption in the visible range, but have higher lying LUMO energy levels (lower reduction potentials) than perylene diimides. [12] This enables reaching of higher open circuit voltages (V OC ) in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…With the sterically hindered drug Chl attached, the π-π stacking effect of CPMI was weakened. 41,42 As a result, NPMI easily aggregated into larger particles. Therefore, the release of NPMI upon the TME response would induce the size-enlargement of the nanodrug.…”
Section: Preparation Of the Nanodrugmentioning
confidence: 99%
“…In recent works, , we already prepared A-D-A type acceptors comprising perylene monoimide (PMI) as end groups and electron rich donors (fluorene, carbazole, indenofluorene). PMI derivatives have not only a strong UV–Vis absorption and high thermal and photochemical stability but can also be modified easily due to their straightforward synthetic preparation. , By switching the side chain on the linker to diethylene glycol, we already showed that the permittivity can be improved . Here, we shifted our focus to sulfone-based side chains.…”
Section: Introductionmentioning
confidence: 99%